The Utility of Chest X-ray vs Computed Tomography in Febrile Neutropenic Patients Presenting to Oncology Unit of the Tertiary are Hospital. - Naz, Shaista; Manzoor, Rabiha; Shamraiz, Ifnan; Bibi, Ayesha; Hira, Benish; Latif, Ayesha (Journal of Postgraduate Medical Institute, 2025)
Objective: Our study aimed at comparing the performance of high-resolution computed tomography (HRCT) and chest X-ray (CXR) in diagnosing febrile-neutropenic (FN) patients having childhood malignancies. Methodology: This cross-sectional, prospective study included children having febrile neutropenia who had malignancies presenting at the pediatric oncology unit of Combined Military Hospital, Rawalpindi from 1st January 2022 to 30th June 2023. Total 114 children, up to 18 years having fever of 38.2°C or more and absolute neutrophil count <1000/µl, were included. Chest x-ray and HRCT were done to document the pulmonary lesions and findings were compared. Results: CXR findings were normal in 64.9% and abnormal in 35.1%, while 84.2% had abnormal findings on HRCT and 15.8% were normal (p=0.001). HRCT findings were statistically significant in patients with ANC≤0.5 as compared to ANC >0.5 (p=0.005). Conclusion: HRCT is supercilious to CXR in determining pulmonic lesions in patients with febrile neutropenia. In severe neutropenic patients with fever, irrespective of respiratory symptoms, HRCT should be done. It can help to initiate timely proper treatment and reduce the morbidity and mortality.